2021
DOI: 10.1021/acs.macromol.1c00441
|View full text |Cite
|
Sign up to set email alerts
|

Taming Charge Transport and Mechanical Properties of Conjugated Polymers with Linear Siloxane Side Chains

Abstract: A series of conjugated polymers on the basis of diketopyrrolopyrrole and thienothiophene with different lengths of linear hybrid siloxane-terminal side chains were designed and synthesized. The number of silicon atoms in the side chains was 3, 5, and 7 (PTDPPTT-Si-3, PTDPPTT-Si-5, and PTDPPTT-Si-7, respectively, with two accompanying reference polymers, PTDPPTT-Ref-1 and PTDPPTT-Ref-2). Compared with PTDPPTT-Si-3, PTDPPTT-Si-5 and PTDPPTT-Si-7 had longer siloxane-terminal groups, which allowed them to maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 52 publications
0
29
1
Order By: Relevance
“…Conjugated polymers (CPs) have great potential as organic semiconductors for applications in the next-generation electronics because of their flexibility, light weight, and solution processability. The rigid backbones of CPs are generally substituted with flexible side chains, not only to solubilize but also to optimize the conformation and aggregation behavior of the main chain to achieve improved semiconducting performance. For example, hydrophobic fluorinated side chains have demonstrated the ability of isolating atmospheric water/oxygen , and promoting close packing of naphthalene diimide-based CPs for enhanced charge transport property and air stability . The bulky siloxane side chains, even placed farther away from the conjugated backbone, imparted good solubility to the polymers while allowing for tight molecular packing. , In our previous work, by moving the branch point of alkyl side chains away from the diketopyrrolopyrrole backbone, CPs that formed well-aligned films under shear force for organic thin-film transistors (OTFTs) were obtained . Comparative studies confirmed that a favorable branch point position determined the formation of the alignable anisotropic precursor in solution and was critical for improved electrical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated polymers (CPs) have great potential as organic semiconductors for applications in the next-generation electronics because of their flexibility, light weight, and solution processability. The rigid backbones of CPs are generally substituted with flexible side chains, not only to solubilize but also to optimize the conformation and aggregation behavior of the main chain to achieve improved semiconducting performance. For example, hydrophobic fluorinated side chains have demonstrated the ability of isolating atmospheric water/oxygen , and promoting close packing of naphthalene diimide-based CPs for enhanced charge transport property and air stability . The bulky siloxane side chains, even placed farther away from the conjugated backbone, imparted good solubility to the polymers while allowing for tight molecular packing. , In our previous work, by moving the branch point of alkyl side chains away from the diketopyrrolopyrrole backbone, CPs that formed well-aligned films under shear force for organic thin-film transistors (OTFTs) were obtained . Comparative studies confirmed that a favorable branch point position determined the formation of the alignable anisotropic precursor in solution and was critical for improved electrical performance.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Recently, our group has synthesized long, linear siloxane side chains and found that they were effective in improving the solubility of conjugated polymers. [20][21][22][23] The introduction of siloxane side chains also improves the flexibility of the polymer chains and reduces the film crystallinity and elastic modulus, thus significantly enhancing the stretchability of conjugated polymers. [22] However, the effect of the molecular weight on the structure and properties of conjugated polymers with siloxane side chain modifications has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] The introduction of siloxane side chains also improves the flexibility of the polymer chains and reduces the film crystallinity and elastic modulus, thus significantly enhancing the stretchability of conjugated polymers. [22] However, the effect of the molecular weight on the structure and properties of conjugated polymers with siloxane side chain modifications has not been investigated. Therefore, it is important to explore the effect of the molecular weight on the structure and properties of conjugated polymers modified with siloxane side chains.…”
Section: Introductionmentioning
confidence: 99%
“…In methanol solution and thin films (Figures d and S3), PDI-N and PDI-OSi exhibit identical absorption bands in the 400–600 nm range because they have the same conjugated backbone structure. Compared to PDI-N, PDI-OSi displays a diminished vibration intensity of the absorption peak near 300 nm, which signals that the PDI backbone conformation is more bent because siloxane side chains aggrandize the spatial repulsion between the molecular side chains . Compared with the solution state, the absorption wavelengths of the thin-film states of PDI-N and PDI-OSi exhibit a significant red shift (∼83 nm for the former and ∼29 nm for the latter), as shown in Figure d, which is primarily on account of the stacking of the PDI backbone by intermolecular interactions.…”
Section: Resultsmentioning
confidence: 96%